Constructing MoS2/CoMo2S4/Co3S4 nanostructures supported by graphene layers as the anode for lithium-ion batteries. Issue 4 (2nd January 2020) - Wang, Pengcheng; Zhang, Peng; Zheng, Xiaohang; Cao, Jian; Liu, Yang; Feng, Jicai; Qi, Junlei
Abstract : With the increasing energy demand, it is very urgent to develop new anode materials for lithium ion batteries (LIBs). Abstract : With the increasing energy demand, it is very urgent to develop new anode materials for lithium ion batteries (LIBs). Designing nanostructures and constructing multicomponent metal sulfides are vital for enhancing the electrochemical performance. This study reports a new synthetic method to construct MoS2 /CoMo2 S4 /Co3 S4 nanostructures supported by graphene. A key step in the process, high temperature annealing, promotes the interdiffusion of metal sulfides to form multicomponent metal sulfides and establishes a strong C–S bond between the MoS2 /CoMo2 S4 /Co3 S4 nanostructure and graphene. The unique nanostructure and synergistic effects between the conductive graphene and the MoS2 /CoMo2 S4 /Co3 S4 nanostructure endows the material with good lithium storage. As a result, it exhibits a good rate performance (360 mA h g −1 at 10 A g −1 ) and a high specific capacity (770 mA h g −1 at 0.2 A g −1 ). This study provides a unique method to construct promising anode materials for the application of LIBs.